2015
DOI: 10.1016/j.canep.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood types and cancer risk—A cohort study of 339,432 subjects in Taiwan

Abstract: Background The associations of laboratory-based ABO phenotypes with cancer risks and mortality have not been systematically determined. Methods The study subjects were 339,432 healthy individuals with laboratory-based blood types from a Taiwan cohort. Results Compared to blood type O, blood type A was significantly associated with an elevated risk of stomach cancer incidence (Hazard Ratio [HR], 1.38 [95% CI, 1.11–1.72]) and mortality (HR, 1.38 [95% CI, 1.02–1.86]) compared with blood type O, after adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 35 publications
(49 reference statements)
4
33
0
1
Order By: Relevance
“…A cross-sectional study in northern China found that blood type A was associated with statistically significant 30–40% higher risk of intestinal metaplasia or gastric dysplasia, the most advanced pre-malignant lesions in the stomach, in people with blood type A than in those with other blood types [ 15 ]. A recent prospective cohort study in a Taiwanese population showed that blood type A was associated with a 38% increased risk of stomach cancer [ 16 ]. The present study found a 26% increased risk of gastric cancer for blood type A as compared with blood types B and O (HR = 1.26, 95% CI = 1.06–1.51, P = 0.011), consistent with findings of earlier studies in Chinese as well as in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in northern China found that blood type A was associated with statistically significant 30–40% higher risk of intestinal metaplasia or gastric dysplasia, the most advanced pre-malignant lesions in the stomach, in people with blood type A than in those with other blood types [ 15 ]. A recent prospective cohort study in a Taiwanese population showed that blood type A was associated with a 38% increased risk of stomach cancer [ 16 ]. The present study found a 26% increased risk of gastric cancer for blood type A as compared with blood types B and O (HR = 1.26, 95% CI = 1.06–1.51, P = 0.011), consistent with findings of earlier studies in Chinese as well as in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal selection and the principle of glycosidic, phenotypic accommodation explained above have been postulated to contribute to the increased risk of human blood group A individuals developing different types of cancer, and the naturally occurring anti‐A‐reactive isoagglutinins and anti‐Tn‐cross‐reactive antibodies clearly interact with tumor‐associated O ‐glycan structures produced in pancreatic cancer . In a recent cancer risk cohort study, Sun et al . described a statistically significant risk of stomach cancer and pancreatic cancer in blood group A individuals compared with blood group O(H) individuals, while kidney cancer risk was inversely associated with blood type AB.…”
Section: Molecular Relationship Of Human Abo(h) Blood Group Phenotypementioning
confidence: 99%
“…Clonal selection and the principle of glycosidic, phenotypic accommodation explained above have been postulated to contribute to the increased risk of human blood group A individuals developing different types of cancer, 15 and the naturally occurring anti-A-reactive isoagglutinins and anti-Tn-cross-reactive antibodies clearly interact with tumor-associated O-glycan structures produced in pancreatic cancer. 27 In a recent cancer risk cohort study, Sun et al 28 described a statistically significant risk of stomach cancer and pancreatic cancer in blood group A individuals compared with blood group O(H) individuals, while kidney cancer risk was inversely associated with blood type AB. A comprehensive study by Vasan et al 29 showed positive associations in blood group A individuals with cancer of the pancreas, breast, salivary glands, mouth, stomach, and chronic lymphatic leukemia and in blood group B individuals with cancer of the corpus uteri and the bladder; however, inverse associations were observed in blood group A individuals for pharyngeal cancer, esophageal adenocarcinoma, and small intestinal cancer and in blood group B individuals for pleural mesothelioma and myelomas.…”
Section: Molecular Relationship Of Human Abo(h) Blood Group Phenotypementioning
confidence: 99%
“…ABO blood type was first discovered by Karl Landsteiner in 1900 and has been widely studied in various diseases and blood transfusion complications (1). ABO blood type was suggested to be associated with various types of cancer such as lung cancer (2), prostate cancer, bladder cancer (3) and pancreatic adenocarcinoma (4).…”
Section: Introductionmentioning
confidence: 99%